Thermo-Rheological Investigation and Modeling of the Shear Viscosity of Polypropylene above the Melting Temperature - Al-Baldawi, Ammar; Muallah, Shatha K.; Wünsch, Olaf (Al-Khwarizmi Engineering Journal, 2013)
The increasing use of polymeric materials in the daily life, leads to challenges in the processing industry to deliver high performance materials with affordable terms. However, new processing techniques lead to high costs. In order to reduce processing costs it is necessary to understand the non-Newtonian behavior of the polymers in their molten state to be able to simulate the processes before the construction of the plants starts. Here the shear thinning behavior of the viscosity of polymeric melts is essential. Thus, this paper deals with the experimental investigation of the thermo-rheological behavior of the viscosity of one of the most used polymers (Polypropylene) over a wide range of temperatures and shear rates.  Furthermore, a modeling approach of the viscosity via a generalized non-Newtonian law combined with an Arrhenius model is done.